1999
DOI: 10.1016/s0009-9236(99)70135-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial-dependent forearm vascular relaxation in black Americans

Abstract: This study shows impaired endothelial-dependent forearm vascular relaxation as measured by decreased acetylcholine response in black subjects. This impairment in endothelial function may contribute to the increased incidence of hypertension in black subjects compared with white subjects. Mechanisms for this finding warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
1
36
1
Order By: Relevance
“…Endothelial function in normal healthy adults is influenced by variables such as race (17,21), age (22), and prandial state (23). Endothelial dysfunction has been associated with several disease states, including obesity (24), diabetes mellitus (25), and hypertension (26).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function in normal healthy adults is influenced by variables such as race (17,21), age (22), and prandial state (23). Endothelial dysfunction has been associated with several disease states, including obesity (24), diabetes mellitus (25), and hypertension (26).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the forearm circulation have found important racial differences in vasoreactivity, including a higher minimum forearm vascular resistance, depressed vasodilation in response to ␤-adrenergic stimulation, attenuation in cyclic nucleotide-mediated vascular smooth muscle relaxation, depressed postischemic vasodilation, and an increased median effective concentration in response to acetylcholine among African American subjects. [47][48][49][50][51] These studies were all performed in healthy, young or middle-aged volunteer subjects. Our study differs because of its performance in the coronary circulation in subjects with angiographically normal arteries referred because of symptoms suggestive of coronary insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, another study has shown that the response to sodium nitroprusside is normal in blacks similar in age to those in the present study and younger than the population examined by other authors when vasodilatation is assessed by measurement of forearm vascular resistance. 29 To try to explain this discrepancy in the endotheliumindependent NO-mediated vasodilatory response of blacks when assessed by different methods, we reviewed existing literature on assessment of endothelial function. In most of the studies, the findings regarding the endothelium-dependent and endothelium-independent NO mediated vasodilatory responses in a population were consistent, irrespective of the methodology used to assess endothelial function.…”
Section: Discussionmentioning
confidence: 99%